The effect of operational parameters on the properties of thorium uranium oxide produced via oxalates’ coprecipitation - Narges Bagheri; Ferial Nosratinia; Fazel Zahakifar; Taher Yousefi (Scientific Reports)
Abstract Co-precipitation is a widely used technique for producing thorium-based fuels. In this method, the characteristics of the final product are significantly affected by the operating parameters. This study investigates the effects of operational parameters on the properties of thorium ThO2–30 wt%UO2 powder using oxalate precipitation. The parameters examined include the reaction temperature, stirrer type, and precipitant concentration. The results indicate that temperature, as the most important factor, has a profound effect on the size, morphology, and crystallinity of particles. Reducing the temperature produced smaller particles with a more spherical shape and increased agglomeration. Furthermore, the use of an ultrasonic stirrer doubled the particle size, whereas higher oxalic acid concentrations improved particle homogeneity and thickness. The products obtained exhibit particle sizes ranging from 0.4 to 2 μm and specific surface areas between 16 and 36 m2/g. These results demonstrate the importance of precise control over the synthesis conditions of oxalate precipitates. The optimal selection of the operating parameters can significantly improve the physical and structural properties of mixed oxide powders.